2010
DOI: 10.1016/j.neuroscience.2009.09.081
|View full text |Cite
|
Sign up to set email alerts
|

Repeated brief postnatal maternal separation enhances hypothalamic gastric autonomic circuits in juvenile rats

Abstract: Maternal separation of rat pups for 15 minutes each day over the first one to two postnatal weeks (MS15) has been shown to increase the active maternal care received by pups and to decrease their later neuroendocrine and behavioral stress reactivity compared to non-separated (NS) controls. Stress responses prominently feature altered gastric secretion and motility, and we previously reported that the developmental assembly of forebrain circuits underlying gastric autonomic control, including gastric responses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 64 publications
(105 reference statements)
1
30
0
Order By: Relevance
“…Our results, showing differential levels of dorsal BNST Fos activation in response to LiCl treatment across all three rearing groups, suggest that dorsal BNST responsiveness to an interoceptive challenge is altered, in addition to circuit anatomy. More recently, Banihashemi and Rinaman [54] demonstrated increased numbers of gastric pre-autonomic neurons in the PVN in adolescent rats with a developmental history of MS-15, further evidence that central visceral circuits can be altered by early postnatal experience.…”
Section: Discussionmentioning
confidence: 97%
“…Our results, showing differential levels of dorsal BNST Fos activation in response to LiCl treatment across all three rearing groups, suggest that dorsal BNST responsiveness to an interoceptive challenge is altered, in addition to circuit anatomy. More recently, Banihashemi and Rinaman [54] demonstrated increased numbers of gastric pre-autonomic neurons in the PVN in adolescent rats with a developmental history of MS-15, further evidence that central visceral circuits can be altered by early postnatal experience.…”
Section: Discussionmentioning
confidence: 97%
“…These are part of a larger literature showing effects of early life experience, including stress, on later autonomic control of various systems, notably respiratory, cardiovascular, and gastrointestinal systems (Banihashemi and Rinaman 2009;Chung et al 2007;Gue et al 1997;Sanders and Anticevic 2007;Welting et al 2005). However, if we consider only studies that directly measure some aspect of electrophysiological function in autonomic circuitry, only respiratory function has been studied in this way.…”
Section: Generalised Epilepsiesmentioning
confidence: 99%
“…In a previous study [36] , an altered ability of the hypothalamus was suggested to modulate gastric function, including the secretory and motor responses to stress. In agreement with that idea, we also detected alterations in gastric juice volume and acidity.…”
Section: Discussionmentioning
confidence: 97%